Architectural research facing the challenges of the 21st century: Criticality, creativity and diversity - Francisco González de Canales; Ramón Pico Valimaña; José Manuel Almodóvar Melendo (VLC Arquitectura)
As we enter the 21st century, a new era of digital technologies is offering increasing possibilities, but at the same time, posing serious challenges to architectural research. Therefore, the recovery of a critical approach is more necessary than ever. This should encompass not only the critical evaluation of the aforementioned technologies, but also counteract models of thought associated with them, such as the standardization of languages or the hegemony of solutionism. Likewise, it is also necessary to reclaim imagination and brilliance as attributes of a seriously threatened freedom. Working on the challenges of our time must emphasize the ideation, development and definition of mental processes and structures, mechanisms that are still outside the scope of technologies such as Artificial Intelligence. Finally, it is still important to reassert that all architectural postulates should be understood in the cultural environment and physical surroundings in which they are produced, admitting their diversity and avoiding a Eurocentric view. Current environmental degradation can be understood as a symptom of a crisis of civilization, marked by a model of living that does not recognize the need to understand ourselves and our built environment in relation to nature.